Artist residencies in rural Iceland - Gundega Skela 1990- (2021)
In past decades artists’ residencies have experienced exponential and significant growth and consideration around the world. While Iceland is recognized for its culture and arts, most of the scene and activities are concentrated around Reykjavik, the capital area, leaving rural Iceland behind. Artist residencies often play an important role in local communities, but the research on the subject has been very little or none. Therefore, this dissertation seeks to capture artist residency situations in rural Iceland and explore the importance of artist residencies in local communities through in-depth interviews with founders of artist residencies around rural Iceland. Findings of the research indicate that artist residencies in rural Iceland have rather recent history with most of them being established in the last two decades. However, residencies around rural Iceland are very diverse and constantly changing. Art historians as well as respondents of this research are aware and agree on the importance of artist residencies from social, economic, phycological, and other perspectives for all the parties involved in its establishment; therefore, residencies should be considered essential within local and national cultural systems. Most of the residencies are passion-driven voluntary by the founders and therefore, in most of the cases, depend on artist payments to cover the loans or other expenses involved with running the residency. Few reasons behind the minimal financial support and advocacy for residencies in general have been indicated: recent history of the residencies around rural Iceland, lack of communication between the residencies and minimal knowledge about the residencies amongst the public.